EMPRETEC annual report 2012- (UN New YorkUS, 2013)
Presents an overview of the activities carried out by the Empretec Global Network. Emphasises increased South-South collaboration and the impact of Empretec training in building innovative and productive enterprises.
Keywords: ENTREPRENEURSHIP